TINGKAT PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG KEHAMILAN USIA DINI DI KOTA DENPASAR - krisna dewi, dewa ayu dian; Lubis, Dinar (ARCHIVE OF COMMUNITY HEALTH, 2012)
Adolescence pregnancy is a pregnancy among teenage aged between 15-19 years, which commonly occur due to increase of sexsual behaviour before marriage among teenage which may cause unwanted and unintended preganacy. Adolescence pregnancy have a serious impact on health and psychosocial of the adolescents herself and the o? spring. The aim of this study is to know the level of knowledge, a! itude and behavior of Adolescent girls in Denpasar towards adolescence pregnancy. The information is important to understand the risk behavior of teenage girls towards adolescence pregnancy. This study was a descriptive study, using cross sectional method, with samples of 284 teenage girls grade 3 in one private intermediate school in Denpasar. Data was collected by self administered questioner. The results showed that the majority of respondents have high knowledge level (98.6%; n = 280) and moderate knowledge level (1.4%; n = 4) towards adolescent pregnancy. Proportion of good a! itude was 77.8% (n = 221), moderate a! itude is 21.5% (n = 61) and poor was 0.7% (n 2). The result indicate there is a gap beween percentage of students who has a good knowledge (98.6%) with students who has good a! itude level with 98,6% compared to 77,8%. This study showed that the knowledge as predisposing factor of a! itute was not always signi? cantly related with a! itude. Therefore, it is suggested that the school needs to provide counseling program, peer education program and IEC (Information, Education and Communication) to increase skill of the Adolescent girls to prevent adolescent pregnancy.
Keywords: Knowledge, A! itute, Adolescence Female, Adolescence Pregnancy